2001
DOI: 10.1381/096089201321209459
|View full text |Cite
|
Sign up to set email alerts
|

Weight Reduction by Means of Intragastric Device: Experience with the Bioenterics Intragastric Balloon

Abstract: BIB as a means of weight reduction in the obese patient led to a 50.8% loss of excess weight after 6 months. Although severe morbidity can occur, the BIB provides a means for short-term weight reduction in conjunction with dietary measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
74
1
5

Year Published

2004
2004
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(88 citation statements)
references
References 6 publications
8
74
1
5
Order By: Relevance
“…Extensive clinical experience has shown that the complication rate is very low. 5,6,8,9,[15][16][17] In the present study, BIB placement was safe and feasible. In all cases it was positioned after sedation only.…”
Section: -15supporting
confidence: 47%
“…Extensive clinical experience has shown that the complication rate is very low. 5,6,8,9,[15][16][17] In the present study, BIB placement was safe and feasible. In all cases it was positioned after sedation only.…”
Section: -15supporting
confidence: 47%
“…Previously published results revealed an average weight loss of 12-15 kg over 6 months with an excellent safety profile [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] . The Spatz Adjustable balloon was introduced in 2010 as the first IGB approved for 1 year implantation while featuring an adjustability function that afforded balloon volume changes as needed.…”
Section: Introductionmentioning
confidence: 99%
“…It was approved in May 2010 in all 27 countries of the European Union for patients with BMI > 27 that failed previous attempts at weight loss (certificate number 10 0384 QS/NB). The adjustability function was developed to address the issues related to other standard 6 months IGBs; 1) reduced efficacy after 2 to 3 months from implantation 3,16 , and 2) significant nausea, vomiting, and discomfort in the early implantation period, necessitating balloon extraction in 4-7% of patients 1,2 17,18 . In 2012, the Spatz3 adjustable balloon was approved for 1 year implantation with the same features as the original Spatz balloon, but with a softer and smaller profile catheter.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, European trials found patients lose 25-40% of their excess weight after six months [9]. Other studies also find that gastric balloons do cause significant weight loss [10,11], and the amount of weight loss is consistent over studies [1].…”
Section: How Effective Are Gastric Balloons For Weight Loss?mentioning
confidence: 91%